The Exporter Productivity Premium along the Productivity Distribution: First Evidence from a Quantile Regression Approach for Fixed Effects Panel Data Models - Powell, David; Wagner, Joachim (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
An emerging literature on international activities of heterogeneous firms documents that exporting firms are more productive than firms that only sell on the national market. This positive exporter productivity premium shows up in a large number of empirical studies after controlling for observed and unobserved firm characteristics in regression models including firm fixed effects. These studies test for a difference in productivity between exporters and non-exporters at the conditional mean of the productivity distribution. However, if firms are heterogeneous, it is possible that the size of the premium varies over the productivity distribution. In this paper we apply a newly developed estimator for fixed-effects quantile regression models to estimate the exporter productivity premium at quantiles of the productivity distribution for manufacturing enterprises in Germany, one of the leading actors in the world market for goods. We show that the premium decreases over the quantiles – a dimension of firm heterogeneity that cannot be detected through mean regression.
Keywords: Exporter Productivity; Quantile Regression; Fixed Effects; 330 Wirtschaft